2011
DOI: 10.1007/s00405-011-1616-9
|View full text |Cite
|
Sign up to set email alerts
|

Pure-tone auditory threshold in school children

Abstract: To determine pure-tone auditory thresholds, 197 screened children at a typical primary school in a German town (~70,000 inhabitants) were examined. All children underwent a tympanometry and an audiometry at 17 frequencies from 125 to 16 kHz. Regarding age effects, two groups (6-8 and 9-12 years) were analyzed. The cross-sectional research was supplemented by a follow-up study with 35 children of the first graders 3 years later. School children have the poorest hearing sensitivity at low frequencies (below 1 kH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…Many of these studies evaluated representative samples of children, irrespective of middle ear status or hearing history. However, similar effects are seen in data on otologically normal children without a history of acoustic trauma (Buren et al 1992; Haapaniemi 1996; Müller et al 2012). Two studies included otologically normal children approximately 7 years of age: Müller et al (2012) reported thresholds for 6- to 8-year-olds (n=91), and Haapaniemi (1996) reported thresholds for 6- to 9-year-olds (n=156).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Many of these studies evaluated representative samples of children, irrespective of middle ear status or hearing history. However, similar effects are seen in data on otologically normal children without a history of acoustic trauma (Buren et al 1992; Haapaniemi 1996; Müller et al 2012). Two studies included otologically normal children approximately 7 years of age: Müller et al (2012) reported thresholds for 6- to 8-year-olds (n=91), and Haapaniemi (1996) reported thresholds for 6- to 9-year-olds (n=156).…”
Section: Discussionsupporting
confidence: 75%
“…Because both studies reported their results in dB HL, the child-adult difference can be inferred relative to 0 dB HL. While the thresholds reported by Müller et al (2012) are approximately 5 dB higher than those reported by Haapaniemi (1996), the slope of the child-adult difference as a function of frequency was similar. In both cases the child-adult difference dropped by about 5 dB between 250 and 4000 Hz.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, the (slightly) better performance of subjects compared with controls at the exit audiogram is possibly due to a learning effect, most likely from repeated testing, as it has been reported that test scores of pure tone audiometry in children, improve with age or after repeated examinations [2527]. …”
Section: Discussionmentioning
confidence: 99%
“…Due to the occurrence of secreted middle ear otitis during a critical period (when the senses are emerging and adapting to the environment), these impairments can create various disabilities in children. These disabilities can cause behavioral complications in six functional areas: mental maturity, perception, speech and speaking, cognition and general intelligence, academic achievement, and interpersonal behaviors [4, 5]. One of the other impairments is unilateral hearing loss (UHL) that, if not examined, is normally detected later because one of the ears is healthy.…”
Section: Introductionmentioning
confidence: 99%